Spin state transition in LaCoO 3 studied using soft x-ray absorption spectroscopy and magnetic circular dichroism - Haverkort, Maurits W. (Physical review letters, 2006)
Using soft x-ray absorption spectroscopy and magnetic circular dichroism at the Co-L2,3 edge, we reveal that the spin state transition in LaCoO3 can be well described by a low-spin ground state and a triply degenerate high-spin first excited state. From the temperature dependence of the spectral line shapes, we find that LaCoO3 at finite temperatures is an inhomogeneous mixed-spin state system. It is crucial that the magnetic circular dichroism signal in the paramagnetic state carries a large orbital momentum. This directly shows that the currently accepted low- or intermediate-spin picture is at variance. Parameters derived from these spectroscopies fully explain existing magnetic susceptibility, electron spin resonance, and inelastic neutron data.